The Effect of the Work from Home Environment on Work-life Balance and Teachers’ Performance Moderated by Mindfulness Culture - Maristya, Yosuanela Putri; Nurhayati, Mafizatun (Asean International Journal of Business, 2024)
This study aims to analyze the effect of the work from home (WFH) environment on work-life balance (WLB) and teachers’ performance with mindfulness culture as a moderating factor during the Covid-19 pandemic. The research focused on teachers at a private SPK school in Jakarta, with a study population of 134 individuals. A saturated sample technique was employed, and 87 respondents completed the questionnaire. This study was conducted from September to December 2022. The research data were processed and analyzed using SPSS 23 and SmartPLS 3.0. The findings indicate that the WFH environment has a positive and significant impact on teacher performance during the Covid-19 pandemic. Although the WFH environment also has a positive effect on WLB, the P-value shows insignificant results. Furthermore, WLB has a positive and significant influence on teacher performance during the pandemic. Mindfulness culture demonstrates a positive and significant effect on both WLB and teacher performance during the Covid-19 pandemic. However, mindfulness culture was unable to moderate the influence of the WFH environment and WLB on teacher performance. Mindfulness culture acts as a moderator predictor and functions solely as an independent variable.